PO:35:219 | Real-world effectiveness of mepolizumab on gastrointestinal involvement in eosinophilic granulomatosis with polyangiitis and hypereosinophilic syndrome: a multicentre retrospective study: Alessia Gatti1, Francesca Regola1, Giulia Fontana1, Mario Addrea Piga2, Gianluca Moroncini2, Palma Carlucci3, Angelo Vacca3, Paolo Delvino4, Enrico Heffler5, Emanuele Nappi5, Jakub Moll6, Laura Losappio6, Jan Schroeder6, Federica Davanzo7, Roberto Padoan7, Edoardo Conticini8, Paolo Cameli8, Greta Pacini9, Alvise Berti9, Lorenzo Vrola10, Paola Tomietto10, Luca Quartuccio11, Jan Willem Cohen Tervaert12, Sabrina Arnold13, Peter Lamprecht13, Florence Roufosse14, Ilaria Cavazzana1, Franco Franceschini1, Giacomo Emmi15, Paola Toniati1. | 1Rheumatology and Clinical Immunology Unit, ERN ReCONNET, ASST Spedali Civili of Brescia and University of Brescia, Italy, Brescia, Italy; 2Università Politecnica delle Marche and Azienda Ospedaliero Universitaria delle Marche, Ancona, Italy, Ancona, Italy; 3Section of Internal Medicine ’Guido Baccelli’, DiMePRe-J, University of Bari ’Aldo Moro’, Bari, Italy, Bari, Italy; 4Rheumatology Unit, IRCCS San Gerardo dei Tintori, Monza, Italy Monza Italy; 5Department of Biomedical Sciences, Humanitas University and Personalized Medicine, Asthma and Allergy IRCCS Humanitas, Milano, Italy; 6Division of Allergy and Clinical Immunology, ASST GOM Niguarda, Milan, Italy, Milano, Italy; 7Rheumatology Unit, Department of Medicine DIMED, University of Padua, Padova, Italy, Padova, Italy; 8University of Siena, Siena, Italy, Siena, Italy; 9Santa Chiara Hospital and University of Trento, Unit of Rheumatology, Trento, Italy Trento Italy; 10UCO Medicina Clinica, ASUGI, Cattinara Teaching Hospital, Trieste, Italy, Trieste, Italy; 11Division of Rheumatology, Department of Medicine DMED, University of Udine, Udine, Italy, Udine, Italy; 12University of Alberta, Edmonton, Alberta, Canada and Maastricht University, Maastricht, The Netherlands Maastricht The Netherlands; 13Department of Rheumatology and Clinical Immunology, University of Lübeck, Lübeck, Germany Lubeck Germany; 14Department of Internal Medicine, Hôpital Universitaire de Bruxelles - Erasme, Université Libre de Bruxelles, Belgium Brussels Belgium; 15Clinical Medicine and Clinical Immunology and Rheumatology Unit Cattinara University Hospital and University of Trieste, Trieste, Italy. (Reumatismo, 2025)
Background. Eosinophilic gastrointestinal disorders are characterized by marked eosinophilic infiltration of the gastrointestinal (GI) tract causing organ dysfunction and the onset of GI symptoms. They may present in isolation or as part of systemic diseases including eosinophilic granulomatosis with polyangiitis (EGPA) and hypereosinophilic syndrome (HES). Mepolizumab (MEPO), an anti-interleukin-5 monoclonal antibody, is approved for both conditions; however, data are limited regarding its effectiveness in managing GI involvement. This study aims to evaluate MEPO’s effectiveness on EGPA and HES-related GI involvement. Materials and Methods. This was a retrospective cohort study conducted among centres referring to the European EGPA Study Group. Inclusion criteria: age >18 years; EGPA or HES diagnosis; GI manifestations confirmed by histology or imaging; start of MEPO any dosage (100 or 300 mg/month sc, 750 mg/month iv) for uncontrolled GI manifestations. Data were collected from disease onset until MEPO start (t0), at 1 (t1), 3 (t3), 6 (t6), 12 (t12), 24 (t24) months, and during flares (exacerbations of GI symptoms requiring therapeutic escalation). Outcomes included symptom improvement, absolute eosinophil count (AEC) reduction, flare occurrence, and corticosteroid (CS)-sparing effect. Data are presented as n (%) or median (IQR). Wilcoxon or McNemar tests were used as appropriate. Flare rates (flares/patient-month) pre- and post-MEPO were compared using incidence rate ratio (IRR) with 95% CI (p<.05). Results. Forty-eight patients were included. At baseline, all the patients had active GI involvement, with median peak AEC 3857 (1593-9743) cells/mm3. Forty-six patients (96%) had a history of CS use prior to MEPO. Median time from diagnosis to MEPO start was 5 (1-49) months (Table 1). Median AEC decreased by t1 [t0: 805 (482-1805) cells/mm3; t1: 115 (60–223); p<.001] and remained low through t24 [70 (23–108) cells/mm3; p<.001]. By t24, active GI symptoms decreased from 65% to 12% (p<.001) and oral CS (OCS) use from 85% to 46% (p=.001). Median prednisone-equivalent daily dose decreased from 11.3 (5-25) mg/day at t0 to 0 (0-2.5) mg/day at t24 (p<.001) (Table 2). During follow up, 8 patients experienced a GI relapse. All of them were on a stable MEPO dose, with 3 also using OCS (2 tapering) and 1 MMF. Only 1 case of increased AEC was documented. All flares were managed by adjusting CS therapy; MEPO dose was increased from 100 mg to 300 mg/month in 2 cases and immunosuppressive therapy was added in 2 others (Table 3). The flare rate decreased from 0.021 to 0.0049 flares per patient-month after MEPO (IRR 0.23, 95% CI 0.11–0.49, p=.0001), indicating 77% reduction in flare incidence. Conclusions. MEPO effectively controlled GI symptoms in EGPA and HES patients and reduced CS use.